Epigenetic modifications as regulatory elements of autophagy in cancer. Issue 2 (1st May 2015) - Sui, Xinbing; Zhu, Jing; Zhou, Jichun; Wang, Xian; Li, Da; Han, Weidong; Fang, Yong; Pan, Hongming
Highlights Epigenetic modifications play important roles in tumor initiation and development. The role of epigenetics in autophagy is still less well acknowledged. Epigenetic regulation of autophagy emerges as a promising target for cancer therapy.